(untitled) (Agro Productividad, 2023)
Objective: To evaluate the relationships between some technological and nutritional meat quality traits in native Mexican Guajolote (M. g. gallopavo). Design/methodology/approach: In the study, a total of 35 carcasses from male native guajolotes (32-40 weeks old; approximately 2.9 kg carcass weight) were used. Some technological [pH, colour (L*, a*, b*), water-holding capacity (WHC), drip loss (DP), and cooking loss (CL)] and nutritional [dry matter (DM), crude protein (CP), crude fat (CF), crude ash (CA) and energy content (EC)] properties of breast and leg meat were evaluated. Pearson correlation of SAS software was used for data analysis. Results: In breast meat, moderate to high positive correlations (P < 0.01; 0.35 [pH45min vs pH24h] ≤ r ˂ 0.82 [DM vs EC]) were observed, but highly and negatively correlations (P < 0.01; -0.36 [CF vs CA] ≤ r < -0.77 [b* vs DL]) also were found. Similarly, technological and nutritional quality traits in leg meat also showed moderate to high positive correlations (P < 0.01; 0.38 [pH24h vs L*] ≤ r < 0.74 [DM vs CF]); however, high negative correlations (P < 0.01; -0.42 [pH24h vs CL] ≤ r < -0.69 [a* vs b*]) were observed. Limitations on study/implications: Studies on the factors that affect the technological and nutritional characteristics of meat quality in this poultry species should be carried out Findings/conclusions: The results could be used as an important benchmark of the current state of Guajolote meat quality to develop selection and breeding programs in its genetic improvement.